Capturing seasonal variations in faecal nutrient content from tundra herbivores using near infrared reflectance spectroscopy - Mathilde Defourneaux; Laura Barbero-Palacios; Jonas Schoelynck; Noémie Boulanger-Lapointe; James D.M. Speed; Isabel C. Barrio (Science of The Total Environment, 2025)

Long-term changes in herbivore community and vegetation impact of wild and domestic herbivores across Iceland - Mathilde Defourneaux; Isabel C. Barrio; Noémie Boulanger-Lapointe; James D. M. Speed (Ambio, 2024)
Changes in wild and domestic herbivore populations significantly impact extensive grazing systems, particularly in low productive environments, where increasing wild herbivore populations are perceived as a threat to farming. To assess the magnitude of these changes in Iceland, we compiled time series on herbivore populations from 1986 to 2020 and estimated changes in species densities, metabolic biomass, and consumption of plant biomass in improved lands and unimproved rangelands. We compared estimates of consumption rates to past and present net primary production. Overall, the herbivore community composition shifted from livestock to wildlife dominated. However, wild herbivores only contributed a small fraction (14%) of the total herbivore metabolic biomass and consumption (4–7%), and livestock dominated the overall herbivore biomass. These insights highlight the necessity of developing improved local integrated management for both wild and domestic herbivores where they coexist.

The consequences of heatwaves for the reproductive success and physiology of the wingless sub-Antarctic fly Anatalanta aptera - Ella Daly; Mathilde Defourneaux; Camille Legrand; David Renault (Journal of Thermal Biology, 2024)